Economic cooperation in the Greater Mekong subregion : (Asian Development Bank, 1996)
Part I: Overview of Economic Coopference in the Greater Mekong Subregion, Part II: Proceedings of the Fifth Conference on Subregional Economic Cooperation, Part III: Sector Reports.